CHARACTERISTICS OF LITHIUM LANTHANUM TITANATE THIN FILMS MADE BY ELECTRON BEAM EVAPORATION FROM NANOSTRUCTURED La0.67-xLi 3xTiO3 TARGET - Nguyen Nang Dinh; Le Dinh Trong; Pham Duy Long (Universitas Gadjah Mada, 2008)
Bulk nanostructured perovskites of La0.67-xLi3xTiO3 (LLTO) were prepared by using thermally ball-grinding from compounds of La2O3, Li2CO3 and TiO2. From XRD analysis, it was found that LTTO materials were crystallized with nano-size grains of an average size of 30 nm. The bulk ionic conductivity was found strongly dependent on the Li+ composition, the samples with x = 0.11 (corresponding to a La0.56Li0.33TiO3 compound) have the best ionic conductivity, which is ca. 3.2 x 10-3 S/cm at room temperature. The LLTO amorphous films were made by electron beam deposition. At room temperature the smooth films have ionic conductivity of 3.5 x 10-5 S/cm and transmittance of 80%. The optical bandgap of the films was found to be of 2.3 eV. The results have shown that the perovskite La0.56Li0.33TiO3 thin films can be used for a transparent solid electrolyte in ionic battery and in all-solid-state electrochromic devices, in particular.